2018
DOI: 10.1007/s10482-018-1144-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent expression of different guanine-plus-cytosine content 16S rRNA genes in Haloarcula strains of the class Halobacteria

Abstract: Haloarcula strains, which are halophilic archaea, harbour two to three copies of 16S rRNA genes (rrsA, rrsB and rrsC) in their genomes. While rrsB and rrsC (rrsBC) show almost identical sequences, rrsA shows 4-6% sequence difference and 1-3% guanine-plus-cytosine content (P GC ) difference compared to rrsBC. Based on the strong correlation between the P GC of 16S rRNA genes and the growth temperatures of the prokaryotes, we hypothesised that high-P GC rrsA and low-P GC rrsBC are expressed at high and low tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…ruber , and 44.0% for D . radiodurans , respectively, whereas that of the consensus nucleotides was 59.5% (Supplementary Table S2); these tendencies were in agreement with the general rule of temperature adaptation of 16S rRNAs 22,23 . Despite the marked difference in the evolutionary pattern of each individual 16S rRNA, the “cold-adapted” D .…”
Section: Resultssupporting
confidence: 82%
“…ruber , and 44.0% for D . radiodurans , respectively, whereas that of the consensus nucleotides was 59.5% (Supplementary Table S2); these tendencies were in agreement with the general rule of temperature adaptation of 16S rRNAs 22,23 . Despite the marked difference in the evolutionary pattern of each individual 16S rRNA, the “cold-adapted” D .…”
Section: Resultssupporting
confidence: 82%
“…The red pigments were also haloarchaea members ( Haloferax genus) resistant to saturated NaCl (6M). Previous studies have shown that G + C content is associated with genome stability in high saline and abiotic stress [ 55 , 56 , 57 , 58 ]. Thus, it is established that high G + C content in haloarchaeal serves as a protective measure from environmental stress, prevention of thymidine dimers and reduces UV-induced mutations [ 20 , 57 ].…”
Section: Discussionmentioning
confidence: 99%